2013
DOI: 10.1248/cpb.c12-00907
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Dichlorodenafil, an Unapproved Sildenafil Analogue Appearing in Non-prescription Supplements

Abstract: We have developed an efficient synthesis of dichlorodenafil (4), an unapproved sildenafil analogue isolated from dietary supplements. Our sequence employs POCl 3 -mediated chlorination of readily available chloroacetyl compound 7 followed by selective hydrolysis of the chloro-heterocycle function. Our synthesis confirms the structure of the illegal additive, and will provide regulatory agencies with ready access to authentic standard samples of dichlorodenafil (4) to aid in their mission to protect the public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
1
7
1
Order By: Relevance
“…More likely, they are by-products of the synthesis of a sildenafil analogue. For the synthesis of sildenafil and its analogues many different routes are described (Kim et al 2001(Kim et al , 2013Ley et al 2002;Yu et al 2003;Li et al 2004;Xia et al 2005;Abdel-Jalil, Khanfar, Abu-Safieh et al 2005;Medrasi et al 2013). Based on published procedures a hypothetical reaction scheme towards pyrazolopyrimidines bearing an acetyl bridge, explaining the existence of the compounds found in the present study and earlier by others, is shown in Figure 8.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…More likely, they are by-products of the synthesis of a sildenafil analogue. For the synthesis of sildenafil and its analogues many different routes are described (Kim et al 2001(Kim et al , 2013Ley et al 2002;Yu et al 2003;Li et al 2004;Xia et al 2005;Abdel-Jalil, Khanfar, Abu-Safieh et al 2005;Medrasi et al 2013). Based on published procedures a hypothetical reaction scheme towards pyrazolopyrimidines bearing an acetyl bridge, explaining the existence of the compounds found in the present study and earlier by others, is shown in Figure 8.…”
Section: Discussionmentioning
confidence: 51%
“…Seven of them have already been published (piperazinonafil, isopiperazinonafil, oxoacetildenafil, (Z)-/(E)-dichlorodenafil, gendenafil and hydroxyhomoacetildenafil) (Lin et al 2008;Instrumental Analysis Data of Illegal Compounds in Food 2010;Wollein et al 2011;Kim et al 2013). Compound 6 could be assigned to 5-(2-ethoxyphenyl)- Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations